Respuesta :
Answer:
w = -4
Step-by-step explanation:
Step 1: Distribute
-2w - 14 = 2(w + 1)
-2w - 14 = 2w + 2
Step 2: Add 2w to both sides
-2w - 14 + 2w = 2w + 2 + 2w
-14 = 4w + 2
Step 3: Subtract 2 from both sides
-14 - 2 = 4w + 2 - 2
-16 = 4w
Step 4: Divide both sides by 4
-16 / 4 = 4w / 4
-4 = w
Answer: w = -4
Answer:
w=-4
Step-by-step explanation:
First, you open parenthesis to get -2w-14 = 2w+2. Next, you add 2w to each side to get -14 = 4w+2. Then, you subtract 2 from each side to get 4w = -16. Lastly, you divide each side by 4 to get w = -4